PENGARUH MODEL PEMBELAJARAN MIND MAPPING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Ni Kade Ayu Novita Dewi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
IPAS is a learning that prioritizes students' critical thinking skills. However, the lack of use of attractive learning models and media results in students not being interested in participating in social studies learning, so that students' social studies learning outcomes decrease.  This study aims to determine the influence of the Mind Mapping learning model assisted by audio-visual media on the critical thinking skills of grade V students in science learning in elementary school cluster IV, Kediri district for the 2023/2024 school year. The population of this study is all class V in Cluster IV Kediri, with as many as 180 students. This research was conducted using a pseudo-experimental design with a non-equivalent control group. The results of data analysis showed that students who learned with the Mind Mapping model and audio-visual media had a significant increase in critical thinking skills compared to students who did not use this approach. The average score of critical thinking ability of students who used the Mind Mapping learning model was 88.39%, while students who did not use the model only achieved an average score of 80.32%. This shows that the mind-mapping learning model assisted by audio-visual media has a positive impact on the critical thinking ability of grade V students in science lessons in elementary school.